2015
DOI: 10.1016/j.dcn.2015.09.001
|View full text |Cite|
|
Sign up to set email alerts
|

Neurophysiological evidence of an association between cognitive control and defensive reactivity processes in young children

Abstract: Interactions between cognitive control and affective processes, such as defensive reactivity, are intimately involved in healthy and unhealthy human development. However, cognitive control and defensive reactivity processes are often studied in isolation and rarely examined in early childhood. To address these gaps, we examined the relationships between multiple neurophysiological measures of cognitive control and defensive reactivity in young children. Specifically, we assessed two event-related potentials th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 71 publications
4
17
1
Order By: Relevance
“…Similarly, Torpey et al (2013) found that a smaller ERN characterized 6-year-olds who displayed fearful behaviors. Consistent with these results, we recently reported an association between a smaller ERN and higher defensive reactivity, as indexed by a larger startle magnitude to aversive stimuli, in a sample of 3–7 year olds (Lo et al 2015). Nonetheless, the evidence in young children remains limited because there are no investigations examining the relationship between the ERN and concurrent diagnostically-defined symptoms of anxiety disorders using a parent-reported measure that captures the full spectrum of severity across multiple dimensions of anxiety.…”
supporting
confidence: 81%
See 4 more Smart Citations
“…Similarly, Torpey et al (2013) found that a smaller ERN characterized 6-year-olds who displayed fearful behaviors. Consistent with these results, we recently reported an association between a smaller ERN and higher defensive reactivity, as indexed by a larger startle magnitude to aversive stimuli, in a sample of 3–7 year olds (Lo et al 2015). Nonetheless, the evidence in young children remains limited because there are no investigations examining the relationship between the ERN and concurrent diagnostically-defined symptoms of anxiety disorders using a parent-reported measure that captures the full spectrum of severity across multiple dimensions of anxiety.…”
supporting
confidence: 81%
“…Research in healthy adults suggests that a larger ERN is related to better behavioral performance, namely higher accuracy and fewer errors (Gehring et al 1993; Maier et al 2011), supporting theories that propose the ERN serves critical cognitive control functions involved in adaptive behavioral adjustments and error correction (Botvinick and Cohen 2014). Of the few studies in children that have provided data on the association between the ERN and performance, results confirm that a larger ERN is associated with higher accuracy and fewer errors (e.g., Grammer et al 2014; Lo et al 2015). …”
mentioning
confidence: 66%
See 3 more Smart Citations